KEBUTUHAN AGREGAT UNTUK PERKERASAN LENTUR DAN PERKERASAN KAKU (BETON SEMEN) - Furqon Affandi (Direktorat Bina Teknik Jalan dan Jembatan, 2004)
There are two types of pavement that commonly used, namely flexible and rigid pavement. However rigid pavement is relatively new and rarely used in Indonesia compared to the flexible pavement. Meanwhile, there are many parts in Indonesia expriencing difficulty of aggregate for road material. Therefore it need imported from others areas or island. These situations not only lead to the problem of the implementation but also to the high cost of road construction. The paper discuss the need of aggregate for flexible and rigid pavement based on the analysis of pavement thickness design for each type suited to the traffic loading. Discussion indicates that rigid pavement need material not so much as for flexible pavement, just only between 42% and 75% from flexible pavement.